Dipyrromethene as a Ligand for the Stabilization of Low-Valent Gallium Complexes - Richter, Tim; Thum, Stefan; Vilpas, Timothy; Townrow, Oliver; Klerner, Lukas; Langer, Jens; Harder, Sjoerd (Organometallics, 2024)
We investigated the low-valent chemistry of Al and Ga with the ligand tBuDPM, a dipyrromethene ligand scaffold with two large tBu groups in the flanking 1- and 9-positions and a mesityl group in the backbone 5-position. Attempted synthesis of (tBuDPM)AlI by reduction of (tBuDPM)AlI2 with KC8 failed. However, reduction of (tBuDPM)GaI2 (1) with K/KI led to successful isolation of (tBuDPM)GaI (3). The GaII intermediate in the reduction process crystallized as a digallane: [(tBuDPM)GaI]2 (2). Also, 3 crystallized as a dinuclear complex with a Ga-Ga bond. However, in a benzene solution, the 3 dissociates into two mononuclear complexes. Reaction of a benzene solution of (tBuDPM)GaI with excess Me3SiN3 gave the tetrazagallole product (tBuDPM)Ga[N4(SiMe3)2] (4) and not the alternative azide-amide product (tBuDPM)Ga(N3)[N(SiMe3)2], which according to calculations is thermodynamically considerably more stable. Theoretical investigations on the nature of the Ga-Ga bonds in 2 and 3 and the mechanism for selective formation of 4 have been included.
CRIS-Team Scopus Importer:2024-06-28

Redox-active inverse crowns for small molecule activation - Maurer, Johannes; Klerner, Lukas; Mai, Jonathan; Stecher, Hannah; Thum, Stefan; Morasch, Michael; Langer, Jens; Harder, Sjoerd (Nature Chemistry, 2025)
Cyclic crown ethers bind metal cations to form host–guest complexes. Lesser-known inverse crowns are rings of metal cations that encapsulate anionic entities, enabling multiple deprotonation reactions, often with unusual selectivity. Self-assembly of a cycle of metal cations around the multiply charged carbanion during the deprotonation reaction is the driving force for this reactivity. Here we report the synthesis of a pre-assembled inverse crown featuring Na+ cations and a redox-active Mg0 centre. Reduction of N2O followed by N2 release and subsequent encapsulation of O2− demonstrates its reduce-and-capture functionality. Calculations reveal that this essentially barrier-free process involves a rare N2O2− dianion, embedded in the metalla-cycle. The inverse crown can adapt itself for binding larger anions like N2O22− through a self-reorganization process involving ring expansion. The redox-active inverse crown combines the advantages of a strong reducing agent with anion stabilizing properties provided by the ring of metal cations, leading to high reactivity and selectivity. (Figure presented.)
CRIS-Team Scopus Importer:2025-02-28

Selectivity control in the reactivity of dipyrromethene gallium(I) complexes - Richter, Tim; Thum, Stefan; Townrow, Oliver; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Journal of Organometallic Chemistry, 2024)
Following the recent isolation and structural characterization of the first low-valent GaI complex with a monoanionic dipyrromethenide ligand (DPM), herein (DPM)GaI complexes with bulky aryl-substituents in the 1- and 9-positions are described. This study focusses on three DPM ligands with mesityl substituents (MesDPM), 2,6-diisopropylphenyl substituents (DIPPDPM), or 10-isopropyl-9-anthracenyl substituents (iPr-AnthDPM); the synthesis to the latter unknown ligand is described. The precursors (RDPM)GaI2 were obtained by reaction of the corresponding alkali metal complexes (RDPM)M (M = Na or K) with GaI3 and characterized by X-ray diffraction. Crystal structures show the efficient shielding of the GaI2 unit by two flanking aryl groups. In a subsequent reduction step, (DIPPDPM)GaI and (iPr-AnthDPM)GaI have been isolated. Comparison of the crystal structure of (DIPPDPM)GaI with that of a similar β-diketiminate GaI complex shows that the Ga center in the DPM complex is well shielded by flanking DIPP substituents. Despite this favorable ligand geometry, isolation of the corresponding (DPM)Ga=N(SiMe3) complexes failed due to further reaction with a second equivalent of Me3SiN3. This resulted in clean formation of the tetrazagallole complex (tBuDPM)Ga[N4(SiMe3)2] and the amide/azide combination (iPr-AnthDPM)Ga(N3)N(SiMe3)2, both structurally characterized by X-ray diffraction. Selective formation of both complexes shows that the substituents in the DPM ligand effectively control the course of the reaction. DFT calculations show that independent of the substituent (tBu, DIPP, or iPr-Anth) the amide/azide combination is always circa 20 kcal/mol more stable than the tetrazagallole product. The latter must therefore be formed by kinetic control.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Azide; Dipyrromethene ligand; Gallium; Imido; Low-valent

Synthesis, Structure, and Reactivity of a Superbulky low-Valent β-diketiminate Ga(I) Complex - Richter, Tim; Thum, Stefan; Townrow, Oliver; Wiesinger, Michael; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2024)
A low-valent GaI complex with the superbulky β-diketiminate ligand DIPePBDI (HC[C(Me)N−DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl)) was obtained by reduction of (DIPePBDI)GaI2 (1) with KC8 in toluene. Considering that (BDI)GaI and analogue (BDI)AlI complexes are prone to decomposition and can generally only be obtained in low yields (20–40 %), the quantitative formation of (DIPePBDI)GaI (2) is remarkable and no doubt related to its excellent thermal stability even in refluxing toluene. Although the low-valent metal center in 2 is sterically protected by the superbulky DIPePBDI ligand, it is readily oxidized by N2O to give intermediate (DIPePBDI)Ga=O which readily decomposed by abstracting a proton from the backbone Me-substituent. Reaction with trimethylsilyl azide gave an intermediate imido complex (DIPePBDI)Ga=N(SiMe3)2 which reacted with a second equivalent of Me3SiN3 to a mixture of an azide/amido complex (DIPePBDI)GaN3[N(SiMe3)2] (4) and a tetrazagallole complex (DIPePBDI)Ga[N4(SiMe3)2] (5) in a 1 : 2 ratio. Whereas the azide/amido complex 4 could be structurally characterised, the tetraazagallole complex 5 was identified by NMR spectroscopy. DFT calculations on (DIPePBDI)GaI (2) and its reaction products complement this study.
CRIS-Team Scopus Importer:2024-06-07
Keywords: bulky; Gallium; Low-valent; β-diketiminate

Tuning the selectivity of P4 reduction at alkaline-earth metal centres - Thum, Stefan; Townrow, Oliver; Langer, Jens; Harder, Sjoerd (Chemical Science, 2025)
Reduction of P4 with β-diketiminate MgI complexes, (BDI)MgMg(BDI), depends strongly on the bulk of the ligand. Whereas superbulky BDI ligands gave selective reduction to P42− in a butterfly conformation, reduction with a less bulky ligand gave various products among which P84− had a realgar-type structure. The selectivity of P4 reduction can also be controlled by metal choice. Reduction of P4 with CaI synthons of general type (BDI*)Ca-X-Ca(BDI*) in which BDI* is a superbulky ligand and X is a bridging dianion (C6H62− < p-xylene2− < N22−) led to reduction of P4 to the very common, stable Zintl anion P73−. Monitoring this process with 31P NMR shows that cyclo-P42− is an intermediate en route to P73−. Conversion rates increase with increasing reducing power: X = C6H62− < p-xylene2− < N22−. A complex with the weakly reducing DBA2− dianion led to selective P4 reduction to cyclo-P42− (DBA = 9,10-dimethyl-diboraanthracene). DBA inhibits P4-to-P7 conversion, most likely by capturing the electron needed for further P4 reduction by radical processes. Experimental investigations are supported by crystal structure determinations and a computational DFT study which also shows that the nature of metal-P4 bonding (covalent or ionic) determines the preference for formation of butterfly-shaped P42− or planar 6π-electron aromatic cyclo-P42−
CRIS-Team Scopus Importer:2025-02-17